THE CONCEPT OF THE PHENOMENON OF FEAR IN THE HADITHS OF THE INFALLIBLES (PEACE BE UPON HIM): AN ANALYTICAL STUDY - Dahla, Ismail (Milenial, 2024)
Based on the methodology of the purified Sunnah and its benefits to all of humanity, the research addressed the issue of fear and established its goals from a modern perspective on the basis of the noble hadiths reported from the Prophet, the Chosen One, and his family, Khair al-Wari (may God bless him and his family), as the Islamic society, past and present, has deteriorated greatly, in which the scales have been turned, and it has prevailed. It contains corruption, and injustices appear in all aspects of life because of negative fear: which is a person’s fear of creation, and this is naturally in line with the characteristics of an uncertain person, which is relative and varies between people in their societies and environments, and is affected by the circumstances and facts that lead to that fear. He considered it a reprehensible fear, as it is appropriate for the era of the message, and the Messenger (may God’s prayers and peace be upon him and his family) meant “So obey my Messenger, and strive with him if you are believers,” because the believer does not fear anyone but God, so he called for an explanation of the negative energy imposed by planting fear in people’s hearts from The members of one society, which negatively affects societal security and social peace, and studying this in light of hadiths about fear. The research mentioned the meaning of fear linguistically and idiomatically, which referred directly or indirectly to the foundations and structures of man’s relationship with his Creator and with society, and the consequent building of societal peace. And the possibility of developing solutions and treatments for social diseases that cause the spread of fear and the lack of reassurance of individuals in their homes, or in their human communities, by citing examples from the noble hadiths about fear and it meanings: support and significance.